Corrigendum to “Interactions in droplet and particle system of near unity size ratio” [Chem. Eng. Sci. 170 (2017) 154–175] (S0009250917302415) (10.1016/j.ces.2017.03.059)) - Mitra, S.; Evans, G.; Doroodchi, E.; Pareek, Vishnu; Joshi, J. (Pergamon, 2018)
The authors regret that in the above referenced article, there is an error in the Fig. 4b from Section 3.1 titled Transient interaction of droplet on particle at cold state that occurred unintentionally. Fig. 4b presents temporal variation in spread diameter ratio for a low Weber number [Formula presented] case (We ~ 0.9) corresponding to the high-speed visualizations of spreading and recoiling motions of a water droplet shown in Fig. 4a, wherein droplet density ?d= 998.2 kg/m3, droplet impingement velocity at the instant of impact (t = 0) vd,0~ 0.16 m/s, and initial droplet diameter dd,0~ 2.54 mm. The spread diameter ratio, ß is defined as the droplet spread on particle surface normalised by the initial droplet diameter where the time varying droplet spread is determined as the wetted arc length dson particle surface (see Fig. 1 below) which can be written as [Formula presented]where rpis particle radius and f is the arc angle subtended at particle centre, O. In the calculations of Fig. 4b in the article, however, instead of particle radius, diameter was used erroneously which caused the reported spread diameter ratio [Formula presented] to be twice of the actual numbers. After incorporating necessary correction based on particle radius, the revised Fig. 4b (Fig. 2) is presented as follows. Based on this revised figure, the following changes (in bold font) in the description of Fig. 4b in Section 3.1 are intended. This behaviour is quantified in Fig. 4b which presents temporal variations in the spread diameter ratio ds/dd,0where dsdenotes spread diameter of the impacting droplet along the curved periphery of the particle. The average value of the peaks in the experimental trend is ~ 1.0 which remains almost undamped in the first 50 ms of post-impact duration shown in Fig. 4b and reflects the reduced friction arising from hydrophobic nature of the applied coating. This reported anomaly was recently communicated to the authors by Evan Milacic at the Multi-scale Modelling of Multiphase Flows research group, Department of Chemical Engineering and Chemistry, Eindhoven University of Technology, Netherlands, in an expression of interest to use data of this article for his research work. For both general readership and more specific use of the reported research data, authors would like to request the appropriate journal editor to kindly include the revised figure as a corrigendum to this article. The intended change in the figure does not have any impact on rest of the scientific content of the article. The authors would like to apologise for any inconvenience caused in this regard.